Changes and Continuities in the Global Health Governance of Coronaviruses - Sukmawani Bela Pertiwi (Department of International Relations, Universitas Andalas, 2020)
This paper aims to examine changes and continuities in terms of actors and policies in the global health governance on coronaviruses in order to understand the available tools, the characters and the extent they meet the required responses of a pandemic. In doing so, this paper examines actors and policies in the governance of three occurrences of coronaviruses, i.e. SARS, MERS, and the COVID-19. Actors and policies are mapped based on its function in a pandemic: (a) surveillance and knowledge dissemination, (b) material and financial assistance both for emergency and long term purposes, and (c) rule-making behavior. This paper found that the larger scale of the COVID-19 pandemic has led more actors involved in the global governance of COVID-19 than during MERS and SARS. WHO still dominates the surveillance and knowledge dissemination as well as rule making leadership. It also leads in providing material assistance to affected countries. Yet, with the significant impacts to global economy, global financial institutions dominate the provision of financial assistance both for short term and long term commitment. This imbalanced crowd in this last aspect, therefore, causes a changing dominant approach of the GHG on coronaviruses from the previously dominating evidence-based scientific approach to economic approach.